Testimony and Non-Evidential Reasons for Belief (A Non-Purist Place for Interpersonalism) - Rimoldi, Florencia (2024)
Interpersonalist theories of testimony have the theoretical virtue of giving room to the characteristic interpersonal features of testimonial exchange among persons. Nonetheless, it has been argued that they are at a serious disadvantage when it comes to accounting for the way in which testimonial beliefs may be epistemically justified. In this paper, we defend the epistemological credentials of interpersonalism, emphasizing that it is inseparable from the acceptance of non-evidential epistemic reasons to believe, which demands proper conceptual elaborations on the notions of epistemic reasons and of epistemic justification. We offer a proper reading of epistemic reason, and we defend non-purism on justification as the adequate way to conceive the epistemic proposal of interpersonalism on testimony, realizing that only this combination is capable of apprehending certain cases in which there seems to be no way to rule out the idea that the assurance offered by the testifier offers an epistemic reason to believe that it is not evidential.